'Dynasty' in Modern German Intellectual History: Many Concepts, or None?. (4th May 2022) - Gusejnova, Dina
ABSTRACT: This article analyses the conceptual use of terms describing dynastic rule in modern German thought. It examines three topics in which the term 'dynasty' specifically appears: with reference to the non-European empires, European states, and the future of democracy in Germany around 1918. Looking at a range of key thinkers with Max Weber's work as a central reference point, it engages with the question why, despite this wide usage, the influential dictionary Geschichtliche Grundbegriffe does not cover any term describing hereditary rule. The conclusion provides a range of possible explanations for the absence.